O uso do best-seller para o desenvolvimento do letramento literário em sala de aula - Maria Isabel Camargos Nogueira (2022)
Teaching of literature commonly seen in the classroom is increasingly distant from reality and student's taste, so it is necessary to adapt it to the current scenario. Books written to please the 21st century reader and with great sales figures, the best-sellers, are seen with prejudice and judged inferior to canonical works and, therefore, are not considered in the school plan. The present paper seeks to present an alternative to traditional teaching that dialogues with today's youth without the pretension of making a value judgment and comparisons between literary styles. Based on authors such as: Antônio Cândido (2004), Ana Elisa Ribeiro (2019), Marcelo Chiaretto (2014), Núbio Mafra (2013), Graça Paulino (2004), Regina Zilberman (2017), besides normative documents such as BNCC and Currículo Minas Gerais, there is the proposal of contemporary activities such as the proposal of task in pairs, interaction and involvement with social networks and synthesis skills.